Emotional intelligence towards work performance at Johor Education Department / Nurul Atikah Zainal and Nur Syarina Abdul Hakem - Zainal, Nurul Atikah; Abdul Hakem, Syarina (2013)
Emotional intelligence becomes a common problem faced by employees in many organizations today. The purpose of this project is to study the level of emotional intelligence towards work performance at Johor Education Department. Emotional intelligence provide the world with knowledge about how EI can be interpreted as an emotion towards one and another and how it will relate with work performance. It has been the main purpose of this study to use Emotional Intelligence and Work Performance to test it with the employees of Johor Education Department. The employee in the organization which comes from ages range from 25 to 60 years old and from different department. Data is collected through a questionnaire distributed to 161 employees in the Johor Education Department using cluster sampling. The researcher has found that there is a significant relationship between emotional intelligence and work performance among the line workers at Johor Education Department. Based on 3 elements of emotional intelligence, the expression emotion gets the higher score of correlation compare to regulation emotion and utilization emotion. The Statistical Package for Social Science (SPSS) 20 was able to help the researchers to analyze the findings and interpret it. This study is beneficial to the organization because the organization can study whether emotional intelligence will help the organization or individual performance. In addition, it will help them to gain awareness on the most factor of their work performance even the contribution is only in small number. Recommendations for future researches are also having been discussed.